Odpowiedź :
Odpowiedź:
a) (x+1)(x+2)=x²+2x+x+2=x²+3x+2
b) (3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20
c) (2t+1)(1-3t)=2t-6t²+1-3t=1-6t²-t
d) (3ab-7)(3-7ab)=9ab-21a²b²-21+49ab=58ab-21-21a²b²
e) (-x+y)(5x+6y)=-5x²-6xy+5xy+6y²=6y²-5x²-xy
f) (x+5y)(7x-y)=7x²-xy+35xy-5y²=7x²+34xy-5y²
g) (2x⁴-y)(x⁴+y)=2x⁸+2x⁴y-x⁴y-y²=2x⁸+x⁴y-y²
h) (ab-a)(2ab+6a)=2a²b²+6a²b-2a²b-6a²=2a²b²+4a²b-6a²
Szczegółowe wyjaśnienie:
Odpowiedź:
a) x^2 + 2x + x + 2 = x^2 + 3x + 2
b) 3a^2 - 15a + 4a - 20 = 3a^2 - 11a - 20
c) 2t + 6t + 1 - 3t = 5t + 1
d) 9ab - 21ab - 21 - 49ab = -61ab - 21
e) -5x^2 + -6xy + 5xy + 6y^2 = -5x^2 - xy + 6y^2
f) 7x^2 - xy + 35xy - 5y^2 = 7x^2 + 34xy - 5y^2
g) 2x^2 - 2xy - xy + y^2 = 2x^2 - 3xy + y^2
h) 2ab^2 + 6a^2b - 2a^2b - 6a^2 = 2ab^2 + 4a^2b - 6^2
Szczegółowe wyjaśnienie: